Exhausting dance performance and the politics of movement - Lepecki, André 1965- (Routledge, 2006)
The text examines the work of key contemporary choreographers who have transformed the dance scene since the early 1990s in Europe and the USA through their vivid and explicit dialogue with performance art, visual arts and critical theory from the past thirty years, this new generation of choreographers challenge our understanding of dance by exhausting the concept of movement.
Literaturverzeichnis Seite 141-146
Keywords: Geschichte 1990-2004; Beweging (activiteit); Choreografie; Dans; Philosophie; Choreography -- Philosophy; Movement (Philosophy); Movement, Aesthetics of; Ästhetik; Tanz; Europa; USA